IsiXhosa Lexicography: Past, Present and Future - Nkomo, Dion; Wababa, Zola (Lexikos, 2013)
This article presents a panoramic and critical overview of isiXhosa lexicography and its impact on the intellectualisation of this indigenous South African language. The history of isiXhosa lexicography dates back more than two centuries. However, there still exists a need for dictionaries that serve the language-speaking community as practical tools for addressing diverse communication and learning-oriented needs in the current language policy dispensation. The IsiXhosa National Lexicography Unit (XNLU) is currently working on dictionary projects that attempt to address this situation while at the same time not losing sight of the mandate that the Pan South African National Language Board (PanSALB) placed on all the National Lexicography Units (NLUs). For this to happen, the article argues that the NLU needs to put lexicographic practice into its historical perspective, i.e. conceiving dictionary projects in the light of existing dictionaries and lexicographic traditions in the language. Over and above that, there is a need to take into account the recent developments in lexicographic research, adopt co-operative lexicographic practice and develop a dictionary culture among the isiXhosa-speaking community.